The effect of traffic lane widths on the safety of cyclists in urban areas. - Schramm, Amy J.; Rakotonirainy, Andry (Australasian College of Road Safety, 2010)
Der Artikel untersucht die Beziehung zwischen Fahrbahnbreite und Sicherheit der Verkehrsteilnehmer mit dem Fokus auf die Beziehung zwischen motorisierten Verkehr und Fahrradfahrern. Die Untersuchungen zeigen dabei, dass die Fahrbahnbreite unmittelbaren Einfluss auf die Risikowahrnehmung und Geschwindigkeit der motorisierten Verkehrsteilnehmer haben. Die Sicherheit von Fahrradfahrern steigt hingegen, wenn neben festintegrierten Fahrradstreifen ebenfalls die Fahrbahnbreite innerorts grundsätzlich verringert wird.

This literature review examines the relationship between traffic lane widths on the safety of road users. It focuses on the impacts of lane widths on motor vehicle behaviour and cyclists safety. The review commenced with a search of available databases. Peer reviewed articles and road authority reports were reviewed, as well as current engineering guidelines. Research shows that traffic lane width influences drivers perceived difficulty of the task, risk perception and possibly speed choices. Total roadway width, and the presence of on-road cycling facilities, influence cyclists positioning on the road. Lateral displacement between bicycles and vehicles is smallest when a marked bicycle facility is present. Reduced motor vehicle speeds can significantly improve vulnerable road user, particularly pedestrians and cyclists, safety. It has been shown that if road lane widths on urban roads were reduced, through various mechanisms, it could result in a safety environment for all road users.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrssicherheit; Verkehrsinfrastruktur; Verkehrsverhalten; Stadtverkehr; Fahrradinfrastruktur; Unfallvermeidung; Radweg; Fahrbahnbreite; Schutzstreifen; Fahrbahnverengung; Radfahrstreifen; Radverkehrsanlage